Astronaut Radiation Dose Calculation With a New Galactic Cosmic Ray Model and the AMS‐02 Data. Issue 4 (3rd April 2023) - Chen, Xuemei; Xu, Songying; Song, Xiaojian; Huo, Ran; Luo, Xi
Abstract: We present a new calculation of the astronaut dose rate from the galactic cosmic rays in free space at 1 AU. We use the unshielded isotropic fluence‐to‐dose conversion coefficients given in the International Commission on Radiological Protection publication 123. A new 3D and time‐dependent solar modulation model based on Parker's transport equation as originally developed in Song et al. (2021, https://doi.org/10.3847/1538-4365/ac281c ) is used to calculate the galactic cosmic ray spectra at 1 AU. This model uses the recent local interstellar spectra of Corti et al. (2019, https://doi.org/10.3847/1538-4357/aafac4 ), M. J. Boschini et al. (2020, https://doi.org/10.3847/1538-4365/aba901, 2021a, https://doi.org/10.3847/1538-4357/abf11c ) to reproduce the PAMELA and AMS‐02 observations between 2006 and 2019. The radiation dose calculated from our model and from the AMS‐02 spectra in the same rigidity region agrees better than 1% for proton and helium in a time‐dependent way, and at 2% level for six most contributing cosmic ray elements averaged over 7 or 8.5 years. The time‐dependent dose rate analysis over 13 years shows an effective dose equivalent rate of 55–58 cSv/yr at solar minimum (January 2010) and 26 cSv/yr at solar maximum (February 2014). Plain Language Summary: The major goal of the paper is to improve the calculation precision of astronaut radiation dose induced by the energetic cosmic ray from outside the solar system, with the help of the AMS‐02 data. Such uncertainty is large in previous studies based on the early versions of the Badhwar‐O'Neill models (e.g., Badhwar‐O'Neill 2010, 2011, 2014 models). With the recent cosmic ray spectra outside the solar system and more sophisticated simulation, the error of our new model in reproducing the AMS‐02 spectra have globally reduced to ≲2% level, which is subdominant to other error sources in astronaut dose determination. Together with the expected dose caused by an incident particle of certain type and at certain energy from the International Commission on Radiological Protection publication 123, we have set the effective dose equivalent rate range to be between 26 cSv/yr and 55–58 cSv/yr. Key Points: New galactic cosmic ray model for dose calculation Reproduction of the AMS‐02 measured spectra to percent level in a time‐dependent way Time‐dependent dose rate calculation till 2019